2020
DOI: 10.1177/1753425920971032
|View full text |Cite
|
Sign up to set email alerts
|

Kinetics of changes in gene and microRNA expression related with muscle inflammation and protein degradation following LPS-challenge in weaned piglets

Abstract: To test the dynamic changes of the expression of genes and microRNA in the gastrocnemius muscle after LPS challenge, 36 piglets were assigned to a control group (slaughtered 0 h after saline injection) and LPS groups (slaughtered at 1 h, 2 h, 4 h, 8 h, and 12 h after LPS treatment, respectively). After LPS treatment, the mRNA expression of IL-1β, IL-6, and TNF-α reached maximal levels at 1 h, 2 h, and 1 h, respectively ( P < 0.05), and mRNA expression of TLR4, NODs, muscle-specific ring finger 1, and muscle… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

1
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 42 publications
1
2
0
Order By: Relevance
“…Studies have shown that G. parasuis can adhere to and invade different types of epithelial/endothelial cells including PUVEC [47], AOC-45 [48], PBMEC [49], PK-15 [50], NPTr, and SJPL [51], implying a capability of the bacteria to invade the bloodstream for replications and cause severe inflammation in the infected organs. Inflammation often leads to skeletal muscle atrophy [11,52], consistent with the common observation that the body tends to lose weight under pathological or physiological stress.…”
Section: Discussionsupporting
confidence: 71%
See 2 more Smart Citations
“…Studies have shown that G. parasuis can adhere to and invade different types of epithelial/endothelial cells including PUVEC [47], AOC-45 [48], PBMEC [49], PK-15 [50], NPTr, and SJPL [51], implying a capability of the bacteria to invade the bloodstream for replications and cause severe inflammation in the infected organs. Inflammation often leads to skeletal muscle atrophy [11,52], consistent with the common observation that the body tends to lose weight under pathological or physiological stress.…”
Section: Discussionsupporting
confidence: 71%
“…In this study, several metabolism-related processes and pathways were significantly enriched, reflecting metabolic disorders in piglets after G. parasuis infection. Along with the inflammatory response in skeletal muscle, these stress conditions likely trigger the activation of the FoxO pathway and dysregulated miRNA expression [ 52 ]. Previous evidence has shown that activated FoxO signaling pathway and upregulated FOXO1/2/3 can cause skeletal muscle atrophy [ 54 , 55 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation